2012
DOI: 10.1176/appi.ajp.2011.10121823
|View full text |Cite
|
Sign up to set email alerts
|

Religiosity and Major Depression in Adults at High Risk: A Ten-Year Prospective Study

Abstract: Objective Previously the authors found that personal importance of religion or spirituality was associated with a lower risk for major depression in a study of adults with and without a history of depression. Here the authors examine the association of personal importance of religion or spirituality with major depression in the adult offspring of the original sample using a 10-year prospective longitudinal design. Method Participants were 114 adult offspring of depressed and nondepressed parents, followed lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
158
7
9

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 193 publications
(186 citation statements)
references
References 30 publications
10
158
7
9
Order By: Relevance
“…Respondents who attended church monthly, weekly, and more than weekly tended to exhibit slower rates of cognitive decline than those who did not attend church. In a ten year prospective study of offspring of depressed and non -depressed patients, Miller et al (2012) found that a high self-report rating of religion or spirituality may have a protective effect against recurrence of depression, particularly in adults with a history of parental depression.…”
Section: Methodological Issuesmentioning
confidence: 99%
“…Respondents who attended church monthly, weekly, and more than weekly tended to exhibit slower rates of cognitive decline than those who did not attend church. In a ten year prospective study of offspring of depressed and non -depressed patients, Miller et al (2012) found that a high self-report rating of religion or spirituality may have a protective effect against recurrence of depression, particularly in adults with a history of parental depression.…”
Section: Methodological Issuesmentioning
confidence: 99%
“…Their major finding was that self-reported importance of spirituality/religiosity had a -protective effect against recurrence of depression, particularly in adults with a history of parental depression‖, while neither religious attendance nor denomination had a significant predictive effect [36]. This means, the importance a person may ascribe to its spiritual attitude could be of relevance.…”
Section: Discussionmentioning
confidence: 99%
“…An important statement came from Miller and co-workers [36] who followed longitudinally adult offsprings of depressed and non-depressed parents. Their major finding was that self-reported importance of spirituality/religiosity had a -protective effect against recurrence of depression, particularly in adults with a history of parental depression‖, while neither religious attendance nor denomination had a significant predictive effect [36].…”
Section: Discussionmentioning
confidence: 99%
“…However, results from several prospective studies suggest that religious involvement is a predictor of later substance use disorders (Good & Willoughby, 2011;Idler & Kasl, 1997;Lambert et al, 2010;Miller et al, 2012). For example, one prospective study showed that among persons with no AUD at baseline, a higher frequency of organized religious attendance was associated with a lower risk of 6-month AUD incidence (Borders et al, 2010).…”
Section: Discussionmentioning
confidence: 99%